Increase in Nonfatal Digestive Perforations and Haemorrhages Following Introduction of Selective NSAIDs: A Public Health Concern - Barnard, Louise; Lavoie, Dominic; Lajeunesse, Nancy (Drug safety, 2006)
This article documents the impact of the introduction of selective NSAIDs on overall prescription patterns of NSAIDs and associated gastroprotective agents (GPAs), and on the rate of nonfatal digestive perforations and haemorrhages. A retrospective, closed cohort study was conducted using the Quebec Health Insurance Board databases, for a 3-year period overlapping the introduction of selective NSAIDs. All adult subjects who were continuously registered with the Public Prescription Drug Program (PPDP) between 1 January 1999 and 31 December 2001 (n = 2 052 231) were included. Prescriptions for NSAIDs (selective [celecoxib, rofecoxib and meloxicam] and nonselective), concomitant use of GPAs and nonfatal digestive perforations or haemorrhages diagnosed in hospital were compiled. Data were analysed on an annual basis according to age, sex and patient risk of gastrointestinal (GI) complications. The listing of selective NSAIDs in the PPDP formulary was followed by a 28.2% increase in the prevalence of NSAID use from 19.5% in 1999 to 25% in 2001. The proportion of long-term users also evolved rapidly with a 135% increase over 3 years. From 1999 to 2001, there was a 75.9% increase in the rate of nonfatal digestive perforations and haemorrhages in the presence of NSAIDs. The introduction of selective NSAIDs stimulated NSAID use and coincided with an increased incidence of nonfatal digestive perforations and haemorrhages in the presence of NSAIDs. Selective NSAIDs should be prescribed with caution to persons at risk for GI complications.